Early christian creeds (Continuum, 2011)
Provides a study of the rise, development and use of formularies in the creative centuries of the Church's history. This book opens with an examination of creedal elements in the New Testament and features an enquiry into the relation of creeds to the rite of Baptism. It also contains a reconstruction of the expansion of the Roman Creed.
Keywords: Chrześcijaństwo 30-600 (Kościół pierwotny) źródła; Chrześcijaństwo pochodzenie; Teologia dogmatyczna 30-600 (Kościół pierwotny); Wyznanie wiary historia i krytyka